Posttraumatic bilateral thigh Morel-Lavallée lesions without an underlying bone fracture in the United Kingdom: a case report - Sarah Razaq; James Geffner; Asma Khan; Harry Mee; Cynthia Udensi; Fahim Anwar (Journal of Trauma and Injury)
A Morel-Lavallée lesion results from a degloving injury between the muscle fascia and the subcutaneous layer. It is most commonly found in the trochanteric area but can occur at other sites. The treatment of the condition varies according to the medical circumstances, as well as the size and chronicity of the condition. A case of large (18×6 and 10×5 cm) bilateral posttraumatic Morel-Lavallée lesions with no underlying bone fracture is presented; the case occurred in a 49-year-old male patient 4 weeks posttrauma. Ultrasound scans showed bilateral large collections of anechoic fluid, which were aspirated under ultrasound guidance and further managed by compression bandages. There were no further complications. The objective of this case report is to present this unique and educational case, as well as to provide an overview of the pathophysiology, diagnosis, and management of Morel-Lavallée lesions. We conclude by discussing the importance of having a high index of suspicion to ensure early detection and prompt treatment of such lesions to avoid complications.